Measuring ‘Brand Love’ : Understanding the Attitude of Millennials towards Select Brands - Malik, Garima; Guptha, Abhinav (Ushus Journal of Business Management, 2021)
The dynamic environment of markets has forced the market researchers to study customer orientation towards a product and his associations with the brand. Millennial are opinion leaders across all business domains in the society; this emphasizes the importance of this particular segment and their impact on brand equity. Indian business is very dynamic and is continuously being affected by the various changes due to the entry of new foreign players, high technological up gradations and changing consumer needs. Hence it has become very important for the marketers of the brands to make their brands more attractive to gain more loyalists. This study intends to propose the importance of the various factors that are responsible for creating ―brand love‖ in the mind of the consumer and thus make the business of the brand profitable for a long time. The validation of the scales for measurement has been proven through this study and top loved brands have been got from the respondents. Brand Love scales on the various brands in the Indian context have proven that love towards the brand generate a high amount of loyalty and have significant effects through a positive ‗word of mouth‘ comment.